SCHIZOPHRENIA ZIKIR THERAPY BASED ON THE INTERPRETATION OF MAFĀTĪḤ AL-GHAYB - Ibrahim, Nurfadila (Tanzil: Jurnal Studi Al-Quran, 2025)
Modern humans face numerous complex life issues such as sadness, confusion, suffering, existential emptiness, stress, depression, and suicide. They strive to eliminate these problems from their lives, leading many to seek help from specialists to address their mental health concerns. Consequently, they often resort to various medications prescribed by doctors or psychiatrists, which can result in many developing schizophrenia. Schizophrenia is a complex mental illness that affects an individual’s perception, thoughts, and behavior. However, in mental health studies, researchers and psychologists frequently focus more on biological and social aspects, neglecting the spiritual dimension. Therefore, this study aims to present and examine the concept of zikir therapy through the perspective of a prominent Islamic scholar found in Tafsīr Mafātīḥ al-Ghayb, addressing various aspects of human life, including psychological and spiritual issues as discussed by Fakhr al-Dīn al-Rāzī. This research will analyze how al-Rāzī integrates zikir therapy into his interpretation of the Qur’an using a qualitative approach by identifying relevant Qur’anic verses such as Q.S. Yūnus [10]: 57, Q.S. Al-Isrā’ [17]: 82, Q.S. Asy-Syu‘arā’ [26]: 80, and Q.S. Ar-Ra‘d [13]: 28. Fakhr al-Dīn al-Rāzī’s thoughts on mental health emphasize the importance of soul balance and the role of spirituality, offering a rich perspective for therapists addressing schizophrenia through zikir therapy. The concept of soul balance can be linked to zikir therapy efforts in managing chaotic emotions and thoughts in patients with schizophrenia. Meanwhile, the emphasis on spirituality can provide patients with a sense of peace and hope while helping them find meaning in life.